2021
DOI: 10.1021/acsami.1c16351
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Delivery of Reactive Oxygen Species/Glutathione-Responsive Paclitaxel Dimeric Nanoparticles Improved Therapeutic Indices against Metastatic Lung Cancer

Abstract: Chemotherapeutics often failed to elicit optimal antitumor responses against lung cancer due to their limited exposure and accumulation in tumors. To achieve an effective therapeutic outcome of paclitaxel (PTX) against metastatic lung cancer with attenuated systemic and local toxicities, pulmonary delivery of redox-responsive PTX dimeric nanoparticles (NPs) was introduced. PTX dimers conjugated through variable lengths of diacid linkers containing disulfide bonds (−SS−) (i.e., α–PTX–SS–PTX, β–PTX–SS–PTX, and γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 48 publications
0
48
0
Order By: Relevance
“…According to previous studies, [44][45][46] the CA4-SS-Cer NP nanoassemblies were prepared using a one-step nanoprecipitation method. The structure of CA4-SS-Cer allows for its aggregation into uniform-sized NPs in deionized water.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, [44][45][46] the CA4-SS-Cer NP nanoassemblies were prepared using a one-step nanoprecipitation method. The structure of CA4-SS-Cer allows for its aggregation into uniform-sized NPs in deionized water.…”
Section: Resultsmentioning
confidence: 99%
“…Upon exposure to DTT media, the disulfide pendants (−SS−) of the prodrug NPs were degraded, yielding a hydrophilic thiol intermediate (PTX−SH). This could easily hydrolyze the ester bonds located at the β-position (Figure 5A), 4 resulting in an accelerated PTX release profile (∼75− 86% drug release within 24 h) with greater mean dissolution time (MDT) and dissolution efficiency (DE) values (Table 2). The prodrug NPs endowed with distinct redox-triggered drug release properties might be promising for the targeted drug delivery to the lung tumor microenvironments bearing amplified levels of GSH 45 .…”
Section: Synthesis and Characterization Of Pull−cc−ptx And Pull−ss−ptxmentioning
confidence: 99%
“…DAPI, a blue-fluorescent DNA stain, was employed to visualize the cell nucleus. 4 The green fluorescent dots of coumarin 6 were detected within the cell cytoplasm following treatment with various NPs, and the fluorescence intensity was augmented with increasing incubation time from 1 to 4 h (Figure S5A). This indicated that NPs were efficiently internalized into the lung cancer cells and their cellular uptake processes were time-dependent.…”
Section: Stability Of Prodrug Npsmentioning
confidence: 99%
“…After 4 days of intravenous injection of B16F10 cells, mice were treated with PBS, AuNPs, and Au@MPN via intratracheal instillation, which allowed the solutions to distribute throughout the lungs in a physiological manner with high reproducibility, accuracy, and efficacy (Fig. 7A) 37 . As shown in Fig.…”
Section: Inhibition Of Lung Metastasis Through Intratracheal Instilla...mentioning
confidence: 99%